Erechtites hieracifolia: an invasive plant species in peatland habitats of southeastern Poland (Central Europe) - Stadnicka–Futoma, Agata; Jaźwa, Małgorzata; Kata, Konrad; Klichowska, Ewelina (Frontiers in Plant Science, 2025)
IntroductionErechtites hieracifolia is an invasive plant species increasingly colonizing peatland plant communities in Central Europe. Invasive plant species are a growing global concern, as they colonize a wide range of habitats, contributing to biodiversity loss. Anthropogenic activity and climate change intensify this process. Mires are among the most vulnerable ecosystems, as lowering groundwater levels and habitat changes facilitate the penetration of invasive species. The aim of this study was to analyze the floristic composition of peatland plant communities with the presence of E. hieracifolia, including an assessment of potential differences between plots with and without the species. In addition, changes in population size over a 3-year period were evaluated, and new localities of E. hieracifolia in Poland were identified.MethodsIn 2019, a total of 60 phytosociological relevés were taken in 12 peatland patches (six with the presence of E. hieracifolia and six without it). The study was repeated in 2022 on the same patches. A syntaxonomic classification of the plant communities was established. The PERMANOVA method was used to analyze differences in species composition between patches with and without E. hieracifolia. Biodiversity indices (Shannon–Wiener and Simpson) were also compared between these two groups.ResultsE. hieracifolia most frequently occurred in raised bogs with low groundwater levels within the Sphagno recurvi–Eriophoretum vaginati association. Maximum species cover was recorded in patch 11 (25%). Within 3 years, the number of patches with E. hieracifolia increased from six to eight. In some of these patches, an increase in both the species cover and range was observed, indicating ongoing expansion. Statistical analysis revealed significant differences in species composition between patches with and without the presence of E. hieracifolia. A clear association of the species with patches characterized by a more abundant occurrence of Eriophorum vaginatum tussocks was also observed. The Shannon–Wiener and Simpson diversity indices showed slightly lower species diversity in communities with E. hieracifolia, suggesting that habitat changes associated with peatland drying favor its colonization.Discussion/ConclusionsThe results indicate that E. hieracifolia preferentially colonizes degraded habitats characterized by reduced biodiversity. These findings suggest that E. hieracifolia may act as an indicator of peatland degradation, with its expansion facilitated by hydrological changes. The study highlights the need for continuous monitoring of invasive species in peatland ecosystems, as their spread may further accelerate biodiversity loss in these vulnerable habitats.